Role of Information Technology in Distance Education: Addressing Challenges and Ensuring Security in Distance Education during COVID-19 (Journal of Advances and Scholarly Researches in Allied Education, 2020)
There is a crucial part of data specialized particularly data and correspondence advancements in separation instruction during this extreme time of the world COVID-19. It is satisfying the prerequisites of the huge size of students which is preposterous by utilizing customary strategy for instructing. This innovation has different tried apparatuses and advancements to meet the prerequisites of understudies. Its instruments are useful in all periods of the learning cycle like affirmation stage, learning stage, assessment stage just as the accreditation stage. It makes the usage of every one of these stages smooth and advantageous. Anyway because of various kinds of prerequisites in the open and separation learning, there are a few difficulties to be taken in the execution of devices accessible in the field of data innovation. This paper presents issues identified with the product, equipment and organization administrations. It likewise presents security issues identified with credibility, accessibility, secrecy and access control techniques for online administrations.